Fiscal Decentralisation and Services Delivery in Mbarara Central Market. - Ainembabazi, Blair (Kabale University, 2024)
Although fiscal decentralization is often promoted as a means to enhance local governance and improve service provision, its actual impact on security, sanitation, and utility services is not well understood. The purpose of the study was to assess fiscal decentralization and service delivery in Mbarara central market, Mbarara District which suggests that local financial autonomy can enhance the efficient delivery of public services within the market area. The study was guided by specific objectives, which include establishing the role of fiscal decentralization in promoting security, establishing the role of fiscal decentralization in promoting better sanitation and examining the role of fiscal decentralization in ensuring the availability of utility services in Mbarara central market, Mbarara district. The study population of 500 respondents was used in this study. Using simple random and census sampling techniques, a total of 215 respondents were selected to participate in the study. Questionnaires, key informant interviews, and documentary methods of data collection were used in this study. On the availability and quality of services provided to the market vendors, respondents reported that the local government allocates funds towards improving sanitation facilities, security guards in the markets, and public health initiatives. It was found that the local government regularly cleans and maintains toilet facilities used by market vendors. On the availability of utility services provided to the market vendors majority of the respondents strongly agreed that there was good accessibility to clean and safe drinking water in the market by the vendors. The government should ensure that the process of budget allocation is transparent and involves active participation from market vendors, local government officials, and relevant stakeholders.